Study of the External Inverting Process of the Mild Steel Thin-walled Tube. Issue 2 (April 2021) - Zheng, Yuqing; Yang, Minghao; An, Yuanyuan; Hu, Yan; Wang, Fangni
Abstract: The invertube is an ideal energy absorber to improve the crashworthiness of the vehicle skeleton body structure, but the low cost mild steel thin-walled tube often suffers some serious tearing phenomena in the external inverting process on the forming die. In order to investigate the interference factors of external inverting deformation, the optimum parameter of die structure design and the axial resistance force level of thin-walled tube in the external inverting process, a nonlinear finite element explicit dynamic codes were adapted to simulate the plastic inverting process of a mild steel thin-walled tube. The tube has the outer diameter of 60mm and the wall thickness of 2.0mm. The external inverting processes were conducted upon two kinds of round corner dies. Based on the results of previous theoretical analysis, the radius range of the corresponding die were obtained by theoretical calculation. The two die section forms and a series of dies with different round corner radii were also designed to build finite element simulation models. The inverting simulation results show that the optimal induced radii of the dies are within the range of 10.5-11.0mm. Meanwhile, it can be seen that the mild steel thin-walled tube has good formability in the early stage, which is convenient for the subsequent fine shaping of the invertube end. Moreover, the die bears less axial extrusion force, which is conducive to the improvement of the working life of the die. In the last, an ideal alloy steel die with the optimal rounded radius of 10.7mm was manufactured and used to verify the feasibility to finish the invertube manufacturing using mild steel thin-walled tubes. It provides a good simulation technology reference for the die structure design to realize the external inverting of the mild steel thin-walled tube.